The manuscript and iconographic on bellicose postcards: from gentlemanly exaltation to the rejection of the Great War (1914-1918) in France - Stancik, Marco Antonio (Anais do Museu Paulista: História e Cultura Material, 2014)
The paper analyzes messages conveyed by postcards produced and circulated in France during the First World War (1914-1918), with themes referring to the conflict. The intention is to compare the iconographic and textual messages printed with handwritten messages, to display forms of expression and perception of war, used by civilian and military on different occasions.